STRATEGY OF “KIOS-K” CUSTOMER RELATIONSHIP MANAGEMENT IN IMPROVING EXCELLENT SERVICE OF PT ANGKASA PURA I ADISUTJIPTO YOGYAKARTA INTERNATIONAL AIRPORT - Adin Noviana; Bambang Sujarwadi (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2019)
This study analyzes the "Kios-K" customer relationship management (CRM) strategy in improving the excellent service of PT Angkasa Pura I Adisutjipto Yogyakarta International Airport. Using qualitative descriptive methods and interview data collection techniques (7 informants fromairport service users, customer service staff, and PT Angkasa Pura I Yogyakarta's communications and legal section staff), observation, and documentation, data analysis was carried out through the stages of data reduction and presentation, conclusion drawing, and verification. Based on the analysis, it is known that there are stages in the CRM strategy implemented by "Kiosk-K" PT Angkasa Pura I Yogyakarta, namely: (1) continuity marketing, (2) one to one marketing, and (3) partnering program. PT Angkasa Pura I Yogyakarta has implemented a CRM strategy in accordance with the existing stages. Bandara service users are also satisfied with the CRM strategy "Kiosk-K" service that is implemented in accordance with the excellent service standards set forth in the Decree of the Minister of Administrative Reform No. 63/KEP/M.PAN/7/2003. From the results of the analysis it can be concluded that the CRM strategy of "Kiosk-K" PT. Angkasa Pura I Yogyakarta has been implemented well, so that airport service users are satisfied and excellent service is achieved.